Potent Antidiabetic Effects of Rivoglitazone, a Novel Peroxisome Proliferator-Activated Receptor-γ Agonist, in Obese Diabetic Rodent Models - Shoichi Kanda; Ryutaro Nakashima; Kanako Takahashi; Jun Tanaka; Junko Ogawa; Tsuneaki Ogata; Makoto Yachi; Kazushi Araki; Jun Ohsumi (Elsevier, 2009)
The pharmacological effects of rivoglitazone, a novel thiazolidinedione-derivative peroxisome proliferator-activated receptor (PPAR)-γ agonist, were characterized in vitro and in vivo. Rivoglitazone activated human PPARγ more potently compared with rosiglitazone and pioglitazone and had little effect on PPARα and PPARδ activity in luciferase reporter assays. In Zucker diabetic fatty (ZDF) rats, 14-day administration of rivoglitazone decreased the plasma glucose and triglyceride (TG) levels in a dose-dependent manner. The glucose-lowering effect of rivoglitazone was much more potent than those of pioglitazone (ED50: 0.19 vs. 34 mg/kg) and rosiglitazone (ED50: 0.20 vs. 28 mg/kg). In addition, rivoglitazone showed potent antidiabetic effects in diabetic db/db mice. In Zucker fatty rats, rivoglitazone at a dose of 0.1 mg/kg clearly ameliorated insulin resistance and lowered plasma TG levels by accelerating the clearance of plasma TG. Gene expression analysis in the liver and heart of ZDF rats treated with rivoglitazone for 14 days suggested that rivoglitazone may reduce hepatic glucose production and modulate the balance of the cardiac glucose/fatty acid metabolism in diabetic animals. In summary, we showed that rivoglitazone is a potent and selective PPARγ agonist and has a potent glucose-lowering effect via improvement of the insulin resistance in diabetic animal models. Keywords:: thiazolidinedione, peroxisome proliferator-activated receptor (PPAR)-γ, diabetes mellitus, insulin resistance, gene expression